Amyloid spell – A close mimic of transient ischemic attack! (Indian Journal of Case Reports, 2024)
Transient focal neurological episodes, also called amyloid spells occur as recurrent, transient episodes of spreading paresthesia seen in 14% of cerebral amyloid angiopathy (CAA) patients. An 81-year-old gentleman with coronary artery disease and a left ventricular clot was on anticoagulant treatment. He presented with three episodes of tingling in the left fingers spreading to the left arm and left leg, each lasting for 10 min. Magnetic resonance imaging of the brain with susceptibility imaging showed convexity hemorrhage, and curvilinear blooming in sulcal spaces of the right cerebral convexity and left precuneus. Warfarin was stopped. He was treated with clobazam, aspirin, and atorvastatin. He improved, so was discharged after 2 days. Amyloid spells can be confused with transient ischemic attack (TIA) or its mimics and the treatment given for TIA can lead to intracranial hemorrhage in CAA patients. Radiological features aid in the diagnosis of CAA and antiplatelets need to be administered cautiously in patients with suspected TIA.